Pengaruh Aplikasi Komposisi Pupuk NPK dan Konsentrasi Bakteri Fotosintesis terhadap Pertumbuhan dan Perkembangan Anggrek Bulan (Phalaenopsis amabilis) - Ivani, Nanda; Wahyuni, Endang Sri (JURNAL BIOSHELL, 2024)
This study aims to determine the appropriate composition of NPK and concentration of photosynthetic bacteria on the growth and development of lunar orchids. This research was conducted from December to April 2023, in Sukorambi Village, Sukorambi District, Jember Regency, East Java Province. This study used a randomized block design (RBD) with a factorial pattern, the first factor was 3 treatments of NPK composition (K) and the second factor was 3 treatments of photosynthetic bacteria concentration (P) repeated 3 times. So that the total experiment was 27 plants. The treatment used was K1 = NPK 1:1:1; K2 = NPK 1.5:1:1; K3 = NPK 2:1:1 and P0 = control; P1 = 2.5ml/l; P2 = 5 ml/l. The test was carried out with the F test with analysis of variance (ANOVA), if there is a significant difference (F-count value> F-table) then proceed with the 5% DMRT test. The results showed that the composition of NPK and photosynthetic bacteria gave a significant interaction on leaf length. However, they were not significantly different in leaf width, number of leaves, root length, number of roots, and fresh weight.